Plasmacytoid DCs From Patients With Sjögren's Syndrome Are Transcriptionally Primed for Enhanced Pro-inflammatory Cytokine Production - Hillen, Maarten R.; Pandit, Aridaman; Blokland, Sofie L. M.; Hartgring, Sarita A. Y.; Bekker, Cornelis P. J.; van der Heijden, Eefje H. M.; Servaas, Nila H.; Rossato, Marzia; Kruize, Aike A.; van Roon, Joel A. G.; Radstake, Timothy R. D. J. (Frontiers in Immunology, 2019)
Primary Sjögren’s syndrome (pSS) is a systemic auto-immune disease typified by dryness of the mouth and eyes. A majority of patients with pSS have a type-I interferon (IFN)-signature, which is defined as the increased expression of IFN-induced genes in circulating immune cells and is associated with increased disease activity. As plasmacytoid dendritic cells (pDC) are the premier type-I IFN-producing cells and are present at the site of inflammation, they are thought to be key players in pSS pathogenesis. Considering the lack of data on pDC regulation and function in pSS patients, we here provided the first in-depth characterization of pSS pDCs. In addition, a group of patients with non-Sjögren’s sicca (nSS) was included; these poorly studied patients suffer from complaints similar to pSS patients, but are not diagnosed with Sjögren’s syndrome. We isolated circulating pDCs from two independent cohorts of patients and controls (each n=31) and performed RNA-sequencing, after which data-driven networks and modular analysis were used to identify signatures of robustly reproducible transcriptional “signatures” of dysregulated and co-expressed genes. Four reproducible gene signatures were identified, including an IFN-induced gene signature and a ribosomal protein gene-signature, that indicated pDC activation. Comparison with a dataset of in vitro activated pDCs showed that pSS pDCs have higher expression of many genes also upregulated upon pDC activation. Corroborating this transcriptional profile, pSS pDCs produced higher levels of pro-inflammatory cytokines, including type-I IFN, upon in vitro stimulation with endosomal Toll-like receptor ligands. In this setting, cytokine production was associated with expression of hub-genes from the IFN-induced and ribosomal protein gene-signatures, indicating that the transcriptional profile of pSS pDCs underlies their enhanced cytokine production. In all transcriptional analyses, nSS patients formed an intermediate group in which some patients were molecularly similar to pSS patients. Furthermore, we used the identified transcriptional signatures to develop a discriminative classifier for molecular stratification of patients with sicca. Altogether, our data provide in-depth characterization of the aberrant regulation of pDCs from patients with nSS and pSS and substantiate their perceived role in the immunopathology of pSS, supporting studies that target pDCs, type-I IFNs, or IFN-signalling in pSS.